Changes in Etiology of Uveitis in a Single Center in Japan. (4th July 2021) - Kunimi, Keiko; Usui, Yoshihiko; Tsubota, Kinya; Mitsuhashi, Ryosuke; Umazume, Akihiko; Kezuka, Takeshi; Sakai, Junichi; Goto, Hiroshi
ABSTRACT: Purpose : We investigated the changes in etiology of uveitis at the Uveitis Clinic of Tokyo Medical University Hospital in recent years. Methods : Medical records of patients with uveitis diagnosed between 2011 and 2017 (Group A) and between 2001 and 2007 (Group B) were reviewed. Results : 1, 587 patients in group A and 1, 507 patients in group B were analyzed. For noninfectious uveitis, frequencies of Vogt-Koyanagi-Harada disease, intraocular lymphoma (IOL) and iridocyclitis in young girls increased, while those of sarcoidosis and Behçet's disease decreased in the recent era. For infectious uveitis, herpetic iridocyclitis, ocular toxoplasmosis, ocular syphilis, and bacterial endophthalmitis increased, while acute retinal necrosis and ocular toxocariasis decreased. Unclassified uveitis decreased, whereas infectious uveitis and IOL increased due to the availability of new diagnostic tests. Conclusion : Etiologies of uveitis have changed over the years. Further development of novel tests and diagnostic criteria would increase definitive diagnosis for unclassified uveitis. (147/150 words)